2012
DOI: 10.1111/j.1440-1819.2012.02341.x
|View full text |Cite
|
Sign up to set email alerts
|

Resting motor threshold changes and clinical response to prefrontal repetitive transcranial magnetic stimulation in depressed patients

Abstract: Aims:  Several variables are able to influence the antidepressant effects of repetitive transcranial magnetic stimulation (rTMS), particularly the intensity of stimulation, which is generally expressed according to the resting motor threshold (RMT). The aim of our study was to investigate whether or not RMT changes during the treatment of resistant depression by rTMS and whether these fluctuations could alter treatment outcome. Methods:  Seventy‐five inpatients suffering from unipolar or bipolar treatment‐resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…As shown in recently published studies, however, rMT does not appear to be a static variable and changes in motor cortex excitability are implicated, similar to previous results. 3,6,7 The present results suggest that VNS affects the motor cortex by increasing motor excitability, thereby reducing rMT. This reduction should be discussed as a significant indicator of increased responsiveness of the frontal and motor cortex due to VNS.…”
supporting
confidence: 54%
“…As shown in recently published studies, however, rMT does not appear to be a static variable and changes in motor cortex excitability are implicated, similar to previous results. 3,6,7 The present results suggest that VNS affects the motor cortex by increasing motor excitability, thereby reducing rMT. This reduction should be discussed as a significant indicator of increased responsiveness of the frontal and motor cortex due to VNS.…”
supporting
confidence: 54%
“…1). [13, 14, 16-18, 20, 22, 24, 25, 28, 29, 31-35, 37-45, 47, 49, 50, 59] Twenty-five studies include experiments that examined neurobiological predictors of response at baseline, [13-17, 19-24, 26-35, 37, 42, 44, 59] six studies included experiments that examined changes to neurobiological factors pre-post a course of rTMS, [18,25,36,41,49,51] and 10 studies examined both a baseline predictor and pre-post experiment. [15, 24-46, 48-51, 59] Four studies investigated only the effects of low-frequency right-sided (LFR) rTMS, [21,27,36,48] whereas eight studies investigated the effects of LFR and high-frequency left-sided (HFL) rTMS combined.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…[38] In terms of TMS neurophysiology for motor cortex, resting motor threshold variations played a role in conferring treatment outcome. [25,36] Larger size of right-sided motor evoked potential (MEP), and longer duration of left side cortical silent period (CSP) at baseline were associated with poorer clinical response after bilateral rTMS, whereas larger short-interval intracortical inhibition (SICI) was associated with poorer clinical response post HFL-rTMS. [19] Here, MEP was correlated with motor excitability, CSP is one of the indices of intracortical inhibition assumed to be mediated by gamma-aminobutyric acid-B (GABA B ) receptor function, and SICI mainly reflects cortical inhibition mediated by GABA A receptor.…”
Section: Neurophysiological Factors That Predict Response To Rtmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we found no effects for other excitability measures. Since RMT, ICF and CSP are rather modulated by other neurotransmitters and -receptors, our findings highlight the role of GABAA mediated neurotansmission in rTMS treatment effects in tinnitus [41,42]. We are well aware that this interpretation is highly speculative and needs to be confirmed by further studies, before further conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 75%